Sovereign credit default swap market response to credit rating announcements: an event study on emerging markets - Yılmaz, Erdem Doğukan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
Credit risk assessments by credit rating agencies and credit default swap (CDS) spreads are the leading indicators of credit risk. Extant literature examined CDS market response to credit rating announcements by credit rating agencies for corporate entities and mostly for developed markets. Few studies, however, investigated the relationship between CDS market and credit rating announcements for sovereign entities. The current study investigates the effect of credit rating announcements on emerging market sovereign CDS spreads and analyzes whether credit rating announcements are anticipated by the CDS market within a period of thirteen years starting from 2001. Event study methodology is used to assess the impact of the credit rating events on sovereign CDS spreads of twenty emerging markets. The results reveal that emerging market CDS spreads respond significantly to positive rating announcements. On the other hand, no significant responses were found for negative rating announcements, implying that the reactions of CDS spreads to credit rating announcements are not symmetrical for positive and negative rating announcements. Additionally, results suggest that both positive and negative rating announcements are anticipated by the CDS market for the entities studied.
Keywords: Credit ratings.; Risk assessment.